ROLE OF Ki 67 AS A PROGNOSTIC MARKER AND THE DIAGNOSTIC VALUE OF IMMUNOHISTOCHEMISTRY IN OVARIAN GRANULOSA CELL TUMORS - LAVANYA RAJAGOPAL,; RAMESH S,; LAVANYA RAJAGOPAL, (International Journal of Pharma and Bio Sciences, 2016)
Granulosa cell tumor (GCT) is a sex cord ovarian neoplasm comprising 1-2% of all ovarian tumors. Even though GCT usually has good prognosis, it is a tumor of unquestionable malignant potential and has a tendency for late relapse. The recurrence rate is 10 -15% for stage IA tumors and 20-30% overall. GCT grows slowly and metastases are often detected more than 5yrs after initial treatment. . Factors related to a relatively poor prognosis include age over 40 years at the time of diagnosis, large tumor size (>5 cm), bilaterality, tumor rupture, mitotic activity and atypical. This 3 year prospective study was conducted on 200 ovarian neoplasms out of which 15 cases were sex cord stromal tumors. Among 15 cases, 10 were histopathologically diagnosed as GCT. The purpose of this study is to know the significance of proliferative marker Ki 67 to predict the prognosis and immunohistochemical markers for the accurate diagnosis of GCT. In the present study, Ki 67 index was higher in 2 cases of GCT (7.9% and 8.4%) which correlated clinically with higher stage [FIGO stage I(c) disease]. Ki 67 index in the rest of the GCT was low which correlated clinically with FIGO stage I (a) disease. Immunohistochemical marker study done in all these cases for confirmation. Out of the ten cases which were histopathologically diagnosed as GCT, two cases turned out to be primary ovarian carcinoid and poorly differentiated carcinoma respectively after immunohistochemical study. The determination of growth fraction using Ki- 67 index is a simple method which provides insight into nuclear proliferation and to predict the clinical behaviour of GCT which are likely to behave in a malignant fashion necessitating a close and long-term follow-up. Immunohistochemical markers like vimentin, inhibin,ki67 are essential for accurate diagnosis of GCT.